Dark blood ebook - Feehan, Christine (Dark, 2014)
The fates of a warrior reborn and a seductive Dragonseeker are irrevocably entwined in this thrilling Carpathian novel by #1  New York Times  bestselling author Christine Feehan. Zev Hunter was an elite warrior, a dark-blood dealer of death to Lycans who preyed on mankind. But he begins to question his past when he awakens in the sacred cave of warriors—and is soothed back to consciousness by the sensuously familiar voice of the woman who has haunted his fantasies for centuries: Branislava, member of the Dragonseeker clan. Now, with a blood-sworn vow of honor, mercy and endurance, and under the influence of a siren as bewitching as Branislava, Zev begins to wonder what his purpose is, what it means for the future of the Carpathians and what it is about his rebirth that he has to fear... INCLUDES BONUS CONTENT!